2008
DOI: 10.1242/jeb.018739
|View full text |Cite
|
Sign up to set email alerts
|

Single unit responses to skin odorants from conspecifics and heterospecifics in the olfactory bulb of crucian carp Carassius carassius

Abstract: SUMMARYInjured fish skin leaks alarm substances that induce the fright reaction upon olfactory detection. The skin also contains a multitude of other odorants traditionally related to other behaviors, but to what extent they are detected upon injury is unknown. We have performed single unit recordings in the olfactory bulb (OB) of crucian carp while exposing the olfactory epithelium to skin extracts from conspecifics and three other species of the carp family, common carp, tench and bream. The aims were to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…Moreover, Lastein et al . 53 found that treatment of crucian carp with corticotrophin-releasing factor antagonist before exposure to conspecific skin extracts suppressed the alarm reaction, supporting the hypothesis that cortisol plays a role in the antipredator response displayed to alarm odours. Since cortisol has been shown to heighten neurological activity and speed decisions on simple or well-rehearsed tasks 5456 , moderate levels of cortisol should enhance vigilance 52 and the speed of the fast-start response.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, Lastein et al . 53 found that treatment of crucian carp with corticotrophin-releasing factor antagonist before exposure to conspecific skin extracts suppressed the alarm reaction, supporting the hypothesis that cortisol plays a role in the antipredator response displayed to alarm odours. Since cortisol has been shown to heighten neurological activity and speed decisions on simple or well-rehearsed tasks 5456 , moderate levels of cortisol should enhance vigilance 52 and the speed of the fast-start response.…”
Section: Discussionsupporting
confidence: 52%
“…TLC was selected because bile salts have been shown to be potent odorants for salmonids (Døving et al, 1980), crucian carp (Lastein et al, 2008) and catfish (Rolen and Caprio, 2007), and are considered to activate ciliated sensory neurons (Thommesen, 1983). Bile salts have been suggested to play a role in the homing behaviour of salmonids (Døving et al, 1980), and bile salts have been shown to act as migratory pheromones for the sea lamprey (Bjerselius et al, 2000;Fine and Sorensen, 2005;Fine et al, 2004;Sorensen et al, 2005).…”
Section: Ligandmentioning
confidence: 99%
“…Interestingly, neurons in the dorsomedial field that project to the habenula, an important structure in the mediation of behavioural responses to CAS (see below), do not show increased fos expression after alarm substance (DeCarvalho et al ., ). In C. carassius , crypt cells project preferentially towards the ventral OB (Hamdani & Døving, ); nonetheless, single‐unit responses to CAS were observed mainly in the dorsomedial field as well (Lastein et al ., ). Extracellular recordings of nervous activity of units composed of mitral cells in the alarm region of the OB during concomitant stimulation at the olfactory epithelium by skin extracts, showed that several of these units respond to (and discriminate between) conspecific and heterospecific skin extracts (Lastein et al ., ).…”
Section: Mechanisms Of Cas Detectionmentioning
confidence: 97%